2011
DOI: 10.1097/rli.0b013e3181f8e8a2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contrast-Enhanced Texture Analysis of the Liver

Abstract: DCE-TA is a potentially useful adjunct to DCE-CT warranting further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…In a study of 17 patients with non-small cell lung cancer, unenhanced CT texture analysis coarse texture uniformity also correlated negatively with tumor stage (16); however, uniformity correlated negatively with the standardized uptake value. Other studies focusing on hepatic texture in patients with colorectal cancer have found a more heterogeneous liver texture at coarse textures is related to the presence of occult malignancy and a poorer prognosis (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 17 patients with non-small cell lung cancer, unenhanced CT texture analysis coarse texture uniformity also correlated negatively with tumor stage (16); however, uniformity correlated negatively with the standardized uptake value. Other studies focusing on hepatic texture in patients with colorectal cancer have found a more heterogeneous liver texture at coarse textures is related to the presence of occult malignancy and a poorer prognosis (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have suggested that these CT texture features may be useful in predicting the clinical outcomes in oncology patients. 4,[6][7][8][9][10]19 In addition, among these texture features, entropy, which reflects the unpredictability of the information content of an image, has been considered to be one of the representative parameters of tumor heterogeneity. 20 In a study by Zhang et al, 8 they reported that increased entropy and skewness on contrast CT images were associated with reduced OS in patients with locally advanced head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Texture analysis assessed on contrast-enhanced CT may be affected by a number of variables. It has previously been shown that pixel values can be influenced by the CT scanners and imaging parameters used, 19 and that for contrast-enhanced CT, the injection rate of contrast media can also affect pixel values. In addition, CT parameters including a large field of view and thick slice thickness (5 mm) can be regarded as suboptimal from a radiologic perspective as it is designed to help plan radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…investigated the use of texture analysis to reveal underlying patterns of change, but with varying degrees of success and rooted in conventional DCE-CT technology (Ganeshan, Burnand et al 2011;Rasmussen 2013).…”
Section: From Regions Of Interest (Roi) To Voxel-based Analysismentioning
confidence: 99%